Vygotskyan analysis of the evolution of electromagnetic concept (Research, Society and Development, 2020)
The aim of this work is to present an analysis of the historical evolution of the initial physical concepts of Electromagnetism, creating a bridge between this branch of Science and the development of learning in the Vygotskian view. This is a bibliographic survey, supported by citations extracted from primary sources of Vygostsky's work. We present an overview of the first developments in Electricity and Magnetism, pointing out the use of models extracted from experiences and concepts already internalized as a fundamental mechanism for the construction of new representations of scientific phenomena. This approach allows us to identify a process of widening and gradually adapting the knowledge constructed by the learner, and the influence of historical and cultural factors, very characteristic of Vygostsky's pedagogical conception. Thus, we identified that the cognitive processes that govern the individual's learning are reproduced, in an analogous way, in the collective sphere of scientific development.